Pengaruh Motif Terhadap Kepuasan Konten Podcast Volix Media Terhadap Generasi Z - Nathasya, Dyan (Jurusan Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jenderal Soedirman, 2024)
New media has provided new opportunities for people to innovate in their work. In addition to the convenience offered in this digital era, digital media has also developed and been used massively both to access information and entertainment. Volix Media was founded in 2021 and has now begun to experience significant development. Volix Media is a digital media company that is engaged in various social media platforms, namely YouTube, Instagram, TikTok, and the Official Website. Volix Media's tagline is